Contribution of Diffusion-Weighted Imaging in the Evaluation of Diffuse White Matter Ischemic Lesions in Fetuses: Correlations with Fetopathologic Findings - Guimiot, F.; Garel, C.; Fallet-Bianco, C.; Menez, F.; Khung-Savatovsky, S.; Oury, J.-F.; Sebag, G.; Delezoide, A.-L. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: The sensitivity of fetal MR imaging is poor with regard to the evaluation of diffuse ischemic white matter (WM) abnormalities. Our purpose was to evaluate the contribution of diffusion-weighted imaging (DWI) in the analysis of microstructural changes in WM and to correlate neuroimaging with neurofetopathologic findings.MATERIALS AND METHODS: We included fetuses with MR imaging, DWI, and a fetopathologic examination. In a region of interest defined by MR imaging, where T1 and T2 intensities were abnormal, the apparent diffusion coefficient (ADC) was measured and immunohistochemical analysis was performed. In fetuses with no WM abnormality in signal intensity, region of interest was defined at random. Histologic reading was performed with a complete blinding of the MR imaging results and ADC values. Three degrees of histologic appearance were defined with regard to vasogenic edema, astrogliosis, microgliosis, neuronal and oligodendrocytic abnormalities, and proliferation or congestion of vessels and were compared with a χ2 test in groups A (normal ADC) and B (increased ADC) fetuses.RESULTS: We included 12 fetuses in group A and 9 in group B, ranging from 29 to 38 weeks of gestation. All group B fetuses and 1 group A fetus demonstrated WM abnormalities in signal intensity. WM edema and astrogliosis were more common in group B than in group A (7/9 vs 2/12 and 8/9 vs 4/12, respectively). No significant difference was observed between both groups with regard to the other parameters.CONCLUSION: This study showed a strong correlation between increased ADCs and 1) WM abnormalities in signal intensity on MR imaging, and 2) vasogenic edema with astrogliosis of the cerebral parenchyma.